On-line enantioseparation of chlorpheniramine using β-cyclodextrin and carbon nanotubes after multivariate optimization - Acosta, Maria Gimena (2013)
Multiwalled carbon nanotubes are evaluated here as solid phase extraction (SPE) sorbent aiming to (±)-chlorpheniramine (CPA) enantioresolution with fluorimetric detection. β-cyclodextrin (CD) was added to the racemate and solutions with HCl and sodium dodecyl sulfate (SDS) in different proportions were assayed as eluents to achieve the separation between both enantiomers. The overall methodology involved a flow injection (FI) strategy enabling high sample throughput and low reagents consumption making it suitable for drug routine quality control. An adequate enantioresolution (2.08) with satisfactory responses for both (R)-CPA (peak area = 285) and (S)-CPA (peak area = 380) was achieved applying the proposed FI-SPE strategy under the optimized conditions [β-CD] = 1.0 mmol L-1, [HCl] = 1.0 x 10-2 mol L-1, [SDS] = 4.0 x 10-4 mol L-1 and eluent flow rate = 8.0 rpm.